Microbiome profiling reveals that Pseudomonas antagonises parasitic nodule colonisation of cheater rhizobia in Lotus. Issue 1 (25th February 2022) - Crosbie, Duncan B.; Mahmoudi, Maryam; Radl, Viviane; Brachmann, Andreas; Schloter, Michael; Kemen, Eric; Marín, Macarena
Summary: Nodule microbiota are dominated by symbiotic nitrogen‐fixing rhizobia, however, other non‐rhizobial bacteria also colonise this niche. Although many of these bacteria harbour plant‐growth‐promoting functions, it is not clear whether these less abundant nodule colonisers impact root–nodule symbiosis. We assessed the relationship between the nodule microbiome and nodulation as influenced by the soil microbiome, by using a metabarcoding approach to characterise the communities inside nodules of healthy and starved Lotus species. A machine learning algorithm and network analyses were used to identify nodule bacteria of interest, which were re‐inoculated onto plants in controlled conditions to observe their potential functionality. The nodule microbiome of all tested species differed according to inoculum, but only that of Lotus burttii varied with plant health. Amplicon sequence variants representative of Pseudomonas species were the most indicative non‐rhizobial signatures inside healthy L. burttii nodules and negatively correlated with Rhizobium sequences. A representative Pseudomonas isolate co‐colonised nodules infected with a beneficial Mesorhizobium, but not with an ineffective Rhizobium isolate and another even reduced the number of ineffective nodules induced on Lotus japonicus . Our results show that nodule endophytes influence the overall outcome of the root–nodule symbiosis, albeit in a plant host‐specific manner.